2011
DOI: 10.1037/a0022251
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation microaggressions: The experience of lesbian, gay, bisexual, and queer clients in psychotherapy.

Abstract: Psychological research has shown the detrimental effects that overt heterosexism have on lesbian, gay, bisexual, and queer (LGBQ) clients and on the psychotherapeutic relationship. However, the effects of subtle forms of discrimination, specifically sexual orientation microaggressions, have on LGBQ clients and the therapeutic relationship have not been addressed. This study used qualitative methodology to explore the phenomenon of sexual orientation microaggressions with 16 self-identified LGBQ psychotherapy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(173 citation statements)
references
References 176 publications
5
164
0
4
Order By: Relevance
“…Studies have found that the process of encountering racial microaggressions can be psychologically and physically draining, often to leading to higher levels of stress and poor mental health outcomes Rivera, Forquer, & Rangel, 2010;Sue, Bucceri, Lin, Nadal, & Torino, 2007;Sue, Capodilupo, & Holder, 2008;Sue, Nadal, Capodilupo, Lin, Torino, & Rivera, 2008). While the most well-known literature on microaggressions has focused on subtle forms of discrimination toward racial and ethnic minority groups (e.g., Nadal, 2011;Pierce, Carew, Pierce-Gonzalez, & Willis, 1973;Sue, Capodilupo, Torino, Bucceri, Holder, Nadal, et al, 2007, Sue 2010, there has been an increase in the literature focusing on microaggressions toward women (Capodilupo et al, 2010;Nadal, 2010), lesbian, gay, bisexual, and transgender (LGBT) people (Nadal, Issa, et al, 2011;Nadal, Rivera, & Corpus, 2010;Shelton & Delgado-Romero, 2011), persons with disabilities (Keller & Galgay, 2010), and religious minorities (Nadal, Issa, Griffin, Hamit, & Lyons, 2010). Despite this increase in the literature, microaggressions based on religion are presently the least studied, which may result in the lack of understanding of their impacts on members of religious minority groups.…”
mentioning
confidence: 99%
“…Studies have found that the process of encountering racial microaggressions can be psychologically and physically draining, often to leading to higher levels of stress and poor mental health outcomes Rivera, Forquer, & Rangel, 2010;Sue, Bucceri, Lin, Nadal, & Torino, 2007;Sue, Capodilupo, & Holder, 2008;Sue, Nadal, Capodilupo, Lin, Torino, & Rivera, 2008). While the most well-known literature on microaggressions has focused on subtle forms of discrimination toward racial and ethnic minority groups (e.g., Nadal, 2011;Pierce, Carew, Pierce-Gonzalez, & Willis, 1973;Sue, Capodilupo, Torino, Bucceri, Holder, Nadal, et al, 2007, Sue 2010, there has been an increase in the literature focusing on microaggressions toward women (Capodilupo et al, 2010;Nadal, 2010), lesbian, gay, bisexual, and transgender (LGBT) people (Nadal, Issa, et al, 2011;Nadal, Rivera, & Corpus, 2010;Shelton & Delgado-Romero, 2011), persons with disabilities (Keller & Galgay, 2010), and religious minorities (Nadal, Issa, Griffin, Hamit, & Lyons, 2010). Despite this increase in the literature, microaggressions based on religion are presently the least studied, which may result in the lack of understanding of their impacts on members of religious minority groups.…”
mentioning
confidence: 99%
“…Although the SMNE subscale was divided into several factors, they are consistent with the authors' concept. One of the extracted scales was based on events witnessed or heard about (SMNE [17][18][19][20][21][22] and the second was focused on HIV (SMNE 23-26). The next one was about events experienced due to an LGB status.…”
Section: Resultsmentioning
confidence: 99%
“…Microagression refers to behaviors resulting from unconsciously maintained prejudices, which are often invisible even to the perpetrator. The consequence of experiencing microagressive behaviors is a deteriorating state of mind that leads to serious mental health problems [14][15][16][17][18].…”
Section: From Physiological To Minority Stressmentioning
confidence: 99%
“…La recherche sur les antécédents et les conséquences des MAHT est encore à un stade embryonnaire (Bostwick et Hequembourg, 2014 ;Platt et Lenzen, 2013 ;Rivera, Nadal et Fisher, 2012 ;Sarno et Wright, 2013 ;Shelton et Delgado-Romero, 2011). Cependant, des études sur les micro-agressions envers les minorités ethnoculturelles montrent leur impact sur la productivité au travail ainsi que sur la santé psychologique et physique, puisqu'elles créent des environnements de travail hostiles et épuisent les ressources cognitives des victimes (p. ex.…”
Section: Les Micro-agressionsunclassified
“…En ce qui concerne l'hétérosexisme et les micro-agressions, les practicien.ne.s doivent prendre conscience de leurs propres a priori, biais et attitudes par rapport aux MSG susceptibles d'interférer avec leurs relations d'aide auprès d'une clientèle LGBT (Nadal, Skolnik et Wong, 2012 ;Shelton et Delgado-Romero, 2011 ;Wright et Wegner, 2012). Reconnaître ses propres limites facilite l'établissement de rela-tions de confiance avec les client.e.s LGBT, ce qui favorise une santé mentale et un développement identitaire optimal.…”
Section: Recommandations Pour Les Milieux De Santéunclassified